2020
DOI: 10.1002/slct.201904912
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Quinoline‐Based Novel Aurones

Abstract: A new series of quinoline based aurones 7(a–n) has been synthesized and evaluated for their antibacterial, antifungal and antiquorum sensing activities. These novel aurones have been prepared directly from 2‐chloro‐1‐(2,4‐dihydroxyphenyl)ethan‐1‐one in one pot, by reacting it with differently substituted 2‐chloroquinoline‐3‐carbaldehydes using activated barium hydroxide under solvent free grinding conditions. Structures of these novel aurones are in agreement with their IR, 1H‐NMR, 13C‐NMR and HRMS data. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 39 publications
1
20
0
2
Order By: Relevance
“…In particular, enlargement of the aromatic area in this position, as in derivatives 10 and 11 ( Figure 3 ), provided the most performing compounds, showing minimal inhibitory concentrations (MICs) in the micromolar/submicromolar range against several pathogen bacteria. Similar functional results were also achieved when the benzofuranone core was replaced with the bioisosteric indolone, as in derivative 12 ( Figure 3 ) [ 20 , 21 , 22 ].…”
Section: Aurones As Functional Agentssupporting
confidence: 63%
“…In particular, enlargement of the aromatic area in this position, as in derivatives 10 and 11 ( Figure 3 ), provided the most performing compounds, showing minimal inhibitory concentrations (MICs) in the micromolar/submicromolar range against several pathogen bacteria. Similar functional results were also achieved when the benzofuranone core was replaced with the bioisosteric indolone, as in derivative 12 ( Figure 3 ) [ 20 , 21 , 22 ].…”
Section: Aurones As Functional Agentssupporting
confidence: 63%
“…52 As a member of the avonoid family, thus far aurones have been reported to possess different bioactivities including antitumor, anticancer, antioxidant, metal ion-chelating, antityrosinase, antiparasitic, antimicrobial, antiviral, anti-inammatory, anti-diabetic, anti-hormonal and anti-obesity activity. 53 They have been found to act as inhibitors for several enzymes such as monoamine oxidase A and B, histone deacetylase and cyclin-dependent kinase, 54 and thus represent an overwhelming and rapidly developing eld in modern heterocyclic chemistry. 55 Considering the literature ndings and in continuation of our previous studies 47,48 aimed at developing new molecules as potent biological candidates, herein, we report the design and synthesis of a new series of chalcones and aurones.…”
Section: Introductionmentioning
confidence: 99%
“…Recently our research group have also reported [49] a series of quinoline based aurones 77 ( a – n ) by treating 2‐chloro‐1‐(2,4‐dihydroxyphenyl)ethan‐1‐one 75 with different 2‐chloroquinoline‐3‐carbaldehydes 76 ( a – n ) in presence of activated barium hydroxide (Scheme 17). The synthesized derivatives were investigated for anti‐biofilm, anti‐fungal and anti‐bacterial activities.…”
Section: Synthesis and Biological Assessmentsmentioning
confidence: 99%